2014
DOI: 10.1371/journal.pone.0106949
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Fungal Species, Quambalaria cyanescens, Isolated from a Patient after Augmentation Mammoplasty – Environmental Contaminant or Pathogen?

Abstract: Some emerging but less common human fungal pathogens are known environmental species and could be of low virulence. Meanwhile, some species have natural antifungal drug resistance, which may pose significant clinical diagnosis and treatment challenges. Implant breast augmentation is one of the most frequently performed surgical procedures in China, and fungal infection of breast implants is considered rare. Here we report the isolation of a rare human fungal species, Quambalaria cyanescens, from a female patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…Q . cyanescens was also reported as an environmental contaminant associated with pseudoepidemic nosocomial pneumonia [ 14 ], and this rare fungus was recently recovered from a female patient after augmentation mammoplasty [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Q . cyanescens was also reported as an environmental contaminant associated with pseudoepidemic nosocomial pneumonia [ 14 ], and this rare fungus was recently recovered from a female patient after augmentation mammoplasty [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quambalaria pusilla is the only species without DNA data available (Beer et al 2006), but it differs morphologically from Q. fabacearum mainly in the size of the conidiophores (5-25 × 1-2 µm), and primary (4-10 × 1-2 µm) and secondary conidia (1.5-3.5 × 0.5-1.5 µm) (Braun 1998). Besides species of Quambalaria being reported as pathogenic to plants, Q. cyanescens is the only species thus far to be associated with human infections, although they are believed to be opportunistic infections, or as a environmental contaminant (Hoog & Vries 1973;Fan et al 2014). Quambalaria fabacearum is reported here as endophyte, representing the first record from Fabaceae.…”
mentioning
confidence: 85%
“…(CMB-W001) indicated a high similarity with Quambalaria cyanescens strains U100 and U105, which were isolated from beetles. 228 The isolation of a rare fungal strain from wasp with taxonomic links to a rare fungus recovered from insects prompted us to undertake a chemical investigation of 230 Quambalaria cyanescens has been isolated from various sources such as plants, 231 from clinical samples 228 and bark beetles. 232 In clinical samples Quambalaria cyanescens was initially regarded as an opportunistic pathogen, however studies have not confirmed a direct correlation between infection and the fungus.…”
mentioning
confidence: 99%
“…232 In clinical samples Quambalaria cyanescens was initially regarded as an opportunistic pathogen, however studies have not confirmed a direct correlation between infection and the fungus. 228 Interestingly, Quambalaria cyanescens has been found in association with different species of beetles around the World including U.S.A, Turkey, Hungary, Bulgaria and Spain. 228 Quambalaria cyanescens has also been isolated from trees of Corymbia spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation